1996
DOI: 10.1051/aas:1996290
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of ionized gas in early-type galaxies. II. The velocity field of the ionized gas

Abstract: A b s tra c t. -We report observations of the velocity field of the ionized gas in the nearby ellipticals NGC 1453, NGC 2974, NGC 3962, NGC 4636, NGC 6868 and NGC 7097. This is part of an ESO Key Programme intended to derive the mass distribution of elliptical galaxies and to investigate the possible presence of dark matter. A ll galaxy spectra are characterized by LINER-type emission. The derived gas kinematics confirm the picture of a regular gaseous disk structure with ordered rotation. The gas velocity dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 17 publications
(22 reference statements)
5
23
1
1
Order By: Relevance
“…This is indeed confirmed by observations, showing regular gaseous disk structures and coherent gas motions (see e.g. Zeilinger et al 1996;Sarzi et al 2006). If most of the clouds were to rotate in the same direction, it would then be rather difficult for them to collide at the high speed required.…”
Section: Comparison With Modelssupporting
confidence: 76%
See 3 more Smart Citations
“…This is indeed confirmed by observations, showing regular gaseous disk structures and coherent gas motions (see e.g. Zeilinger et al 1996;Sarzi et al 2006). If most of the clouds were to rotate in the same direction, it would then be rather difficult for them to collide at the high speed required.…”
Section: Comparison With Modelssupporting
confidence: 76%
“…This scenario cannot be excluded since several studies have found a gaseous component of high velocity dispersion, in the range 150-250 km s −1 , in the center of early-type galaxies (e.g. Bertola et al 1995;Zeilinger et al 1996;Sarzi et al 2006), which translates into higher intrinsic 3D velocity dispersions. This scenario is very appealing since it would naturally explain the observed trends between the emission strength, and the [NII]/Hα ratio, with the galaxy stellar central velocity dispersion.…”
Section: The Ionization Mechanism In Linersmentioning
confidence: 99%
See 2 more Smart Citations
“…Buson et al (1993) and Zeilinger et al (1996) also found that the warm ionized gas is misaligned relative to the stars in NGC 1453, though with a larger misalignment angle of ≈128°.I ti s unlikely that stellar mass loss from the old stellar population is the primary source of the warm ionized medium in NGC 1453 because such recycled gas would tend to remain in the potential well of the stars, leading to photometric and kinematic alignment between the stars and gas.…”
Section: External Accretion Versus Internal Originsmentioning
confidence: 96%